The quest for development success bridging theoretical reasoning with economic practice - Kołodko, Grzegorz W. (Lexington Books, 2021)
"It is an inspiring, interdisciplinary study in the field of social sciences that analyses the most important challenges facing the world economy and modern civilization. Grzegorz W. Kolodko explains in a comprehensible way the contradictions of ideas and interests and practical ways of solving them and its implications for our future"--